Early Age Strength of Development Ultra High-Performance Concrete Using Class-F Fly Ash and Local Materials for Repair - Kharisma Keysia Paramitha; Yuyun Tajunnisa; Wiwik Dwi Pratiwi (Institut Teknologi Sepuluh Nopember, 2024)
Ultra High-Performance Concrete (UHPC) is an innovative material for such repairs because of its superior mechanical properties, strength, crack resistance, and durability. However, its high production cost, primarily due to using materials like silica fume and cement, is a significant drawback. This study explores the feasibility of incorporating fly ash and local materials into UHPCs to reduce costs while maintaining or improving their performance. As a supplementary cementitious material, fly ash enhances the compressive strength and workability of UHPC. The addition of limestone further supports early-age strength and workability. By evaluating the mechanical properties and workability of modified UHPCs, this research demonstrates the economic viability and environmental benefits of structural repairs. The results indicate that this modification can effectively enhance the early-age strength of UHPC, making it suitable for use as a repair material. The evaluation of the mechanical properties and workability of the modified UHPC suggests that these alternative materials can maintain or even improve the performance of UHPC. Thus, this approach offers a more economically viable and environmentally friendly solution for structural repairs.